Time to Kill and Time to Heal: The Multifaceted Role of Lactoferrin and Lactoferricin in Host Defense - Anna Ohradanova-Repic; Romana Praženicová; Laura Gebetsberger; Tetiana Moskalets; Rostislav Skrabana; Ondrej Cehlar; Gabor Tajti; Hannes Stockinger; Vladimir Leksa (MDPI AG, 2023)
Lactoferrin is an iron-binding glycoprotein present in most human exocrine fluids, particularly breast milk. Lactoferrin is also released from neutrophil granules, and its concentration increases rapidly at the site of inflammation. Immune cells of both the innate and the adaptive immune system express receptors for lactoferrin to modulate their functions in response to it. On the basis of these interactions, lactoferrin plays many roles in host defense, ranging from augmenting or calming inflammatory pathways to direct killing of pathogens. Complex biological activities of lactoferrin are determined by its ability to sequester iron and by its highly basic N-terminus, via which lactoferrin binds to a plethora of negatively charged surfaces of microorganisms and viruses, as well as to mammalian cells, both normal and cancerous. Proteolytic cleavage of lactoferrin in the digestive tract generates smaller peptides, such as N-terminally derived lactoferricin. Lactoferricin shares some of the properties of lactoferrin, but also exhibits unique characteristics and functions. In this review, we discuss the structure, functions, and potential therapeutic uses of lactoferrin, lactoferricin, and other lactoferrin-derived bioactive peptides in treating various infections and inflammatory conditions. Furthermore, we summarize clinical trials examining the effect of lactoferrin supplementation in disease treatment, with a special focus on its potential use in treating COVID-19.